Perlindungan Hukum Bagi Korban Atas Publikasi Data Pribadi pada Kasus Tindak Pidana Kesusilaan di Situs Mahkamah Agung - Putri Azzahra; Syarif Nurhidayat (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The publication of decisions through the Supreme Court decision directory is part of the aspect of information disclosure carried out by the Supreme Court as a form of implementation of Law Number 14 of 2008 concerning Public Information Disclosure. This research examines how the protection of personal data of victim witnesses in cases of criminal acts of decency in the publication of decisions by the Supreme Court. Who can be held criminally responsible for the publication of decisions on the Supreme Court website. The legal research method used is normative. In this study it is known that legal protection is not optimal, there are still many main aspects of legal protection that have not been fulfilled such as no further arrangements regarding control efforts, mechanisms for requesting related parties to information disclosure and arrangements regarding the mechanism of legal remedies. Implementers of Information Services at the Supreme Court who can be held criminally responsible for this are PPID Executors, Information Service Officers, PPID, and/or PPID Superiors as employees who have the duties, responsibilities and authority to provide information services to the public in the event that they fulfill errors in the form of intent.